Synthesis, Characterization and Morphological Study of Nicotinamide and p-Coumaric Acid Cocrystal - Mohamad Nor Amirul Azhar Kamis; Hamizah Mohd Zaki; Nornizar Anuar; Mohammad Noor Jalil (Universitas Gadjah Mada, 2020)
Cocrystallization is one of the potent methods used to modify the physicochemical properties of drugs. Cocrystal of nicotinamide (NIC):p-coumaric acid (COU) was synthesized by a slow evaporation method using acetonitrile. The cocrystals with different feed molar ratios (NIC:COU : 1:1, 1:2, and 2:1) were characterized using DSC, PXRD, and FTIR, which revealed the formation of different polymorphs for each feed molar ratio. A single crystal of the NIC:COU (1:1) cocrystal was analyzed using single crystal X-ray diffraction (SCD), and 1H-NMR revealed a greater cocrystal structure stability compared to the previously published cocrystal. The intermolecular hydrogen bonds, N-H···O, and O-H···O interactions played a major role in stabilizing the cocrystal structure. A molecular modeling technique was used for prediction and surface chemistry assessment of the morphology showed an elongated (along y-axis) octagonal crystal shape which was in a reasonable agreement with the experimental crystal morphology. The reduction in values of the cocrystal solubility in ethanol was supported by the DSC data and simulation of crystal facets where most the crystal facets exposed to polar functional groups. At the concentration of 31.3 µM, NIC:COU (1:1) cocrystal showed more effective DPPH scavenging with 77.06% increased activity compared to NIC at the same concentration.